PENGALOKASIAN DANA DESA DAN DAMPAKNYA BAGI PENINGKATAN PENDAPATAN PENDUDUK DESA KESUMBO AMPAI KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS - Ramadhanti, akinah Dara; Sri, Kornita Endang; Ufira, Isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the allocation of village funds and their impact on increasing the income of Kesumbo Ampai villagers, Bathin Solapan Sub District, Bengkalis District. The study population was all families in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency, as many as 885 families. The sampling technique in this study was purposive sampling using the calculation of the Slovin formula so that as many as 90 respondents were obtained. The measurement carried out in this study was to use a questionnaire while the analysis technique was to use descriptive analysis and non-parametric test analysis using the Wilcolxon test using the SPSS program . Based on the results of the study it was found that the allocation of village funds in Kesumbo Ampai Village, Bathin Solapan Subdistrict, Bengkalis Regency was carried out for infrastructure development such as roads, concrete tripe, box colvert, trenches and culverts during 2016 - 2018. The allocation of village funds had an impact on increasing income community in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency. This can be seen from the acquisition of income after the existence of village funds is greater than before the existence of the village fund program, it can be seen from the real value of the income.Keywords: Village Funds, allocation, income